Critical retrospective analysis of various types of neurogenic lower urinary tract dysfunction (NLUTD) at HUSM (2006-2007) - AR, Mosassadeq; AH, Azhar; MD, Mohd Ashraf; Kamarulzaman, Mohd Nazli; Rahman, Mohd Nor Gohar; Z, Mahamood (Universiti Sains Malaysia, 2008)
To find the true incidence of various types of Bladder dysfunction (NLUTD) among neurological, neuro surgical lesions and post OBG status during 2006-2007 at HUSM.